On Privacy-Preserving Protocols for Smart Metering Systems Security and Privacy in Smart Grids - Borges de Oliveira, Fábio; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book presents current research in privacy-preserving protocols for smart grids. It contains several approaches and compares them analytically and by means of simulation. In particular, the book introduces asymmetric DC-Nets, which offer an ideal combination of performance and features in comparison with homomorphic encryption; data anonymization via cryptographic protocols; and data obfuscation by means of noise injection or by means of the installation of storage banks. The author shows that this theory can be leveraged into several application scenarios, and how asymmetric DC-Nets are generalizations of additive homomorphic encryption schemes and abstractions of symmetric DC-Nets. The book provides the reader with an understanding about smart grid scenarios, the privacy problem, and the mathematics and algorithms used to solve it.
Part I: Foundations -- Introduction -- Background and Models -- A Selective Review -- Part II: Contributions -- Reasons to Measure Frequently and Their Requirements -- Quantifying the Aggregation Size -- Selected Privacy-Preserving Protocols -- Analytical Comparison -- Simulation and Validation -- Concluding Remarks.
Keywords: Telecommunication; Data protection; Application software; Cryptography; Data encryption (Computer science).; Communications Engineering, Networks; Data and Information Security; Computer and Information Systems Applications; Cryptology